Pembuatan Pektin dari Limbah Kulit Jeruk Manis (Citrus sinensis) dengan Variasi Volume Pelarut HCl - Amborowati , Cindi; Miana Sari Tinambunan (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2024)
Sweet orange peel waste contains various useful chemical compounds, one of which is pectin. Pectin is a thickening agent commonly used in the food industry. Pectin is obtained by extracting it using acidic solvents. This study aims to determine the effect of HCl solvent volume on the pectin produced. Sweet orange peel was extracted as much as 10 g using 0.5 HCl solvent with solvent volume 300, 400, 500, 600, 700 mL at 90 ˚C for 2 hours. The resulting pectin characteristic testing is compared with IPPA (International Pectin Producers Association) pectin quality standards. The highest yield was obtained at a solvent volume of 400 mL of 11.11%. The water content does not meet the standard because the magnitude is above 12. The characterization of methoxyl levels is classified as high methoxyl because it has a methoxyl value of >7.12 and an esterification degree of >50. Galacturonate levels are high at 54.46% and equivalent weight is low at 388.85 mg. Certain wavenumber results in the FTIR test indicate conformity with the pectin structure